Dietary Supplementation With Yucca Alleviates Heat Stress in Growing Broilers Exposed to High Ambient Temperature - Luo, Jing Jing; Chen, Wei; Qu, Hao; Liu, Yuan Qing; Luo, Cheng Long; Ji, Jian; Shu, Ding Ming; Wang, Jie (Frontiers in Veterinary Science, 2022)
Yucca contains high content of saponin that owns glucocorticord-like effect in animals, e.g. anti-inflammation and anti-microbiota, etc. The objective of the present study was to test the hypothesis that dietary supplementation of yucca powder may alleviate heat stress and improve growth performance of growing broilers subjected to cycling high ambient temperature. A total of two hundred and forty male broiler chicks (Yellow feathered chicken) aged 28 d, with BW of 792 ± 43.7 g, were randomly allocated to one of four treatments (6 replicates per treatment): control (normal temperature, 24 ± 2 oC, 24 h), fed diets supplemented with 100 mg/kg yucca under normal temperature (Y), high ambient temperature exposure (HT, 34 ± 2 oC, 11 h), fed diets supplemented with 100 mg/kg yucca (HT+Y) under high ambient temperature. After 7 d’s adaption, experiment was conducted for 4 weeks (aged 28 – 56 days). HT significantly reduced feed intake, BW and ADG of broiler, but yucca improved the feed intake under HT condition. Yucca supplementation reduced (P < 0.05) the HT-induced increase in temperature of rectum and leg skin. Supplementation of yucca increased the hypothalamic mRNA expression of TRPV2, TRPV4 and TRPM8 (P < 0.05). Yucca reduced (P < 0.05) the plasma lipid oxidation product malondialdehyde (MDA), but did not affect the activities of antioxidant enzyme superoxide oxidase (SOD) and glutathione peroxidase (Gpx). Yucca did not affect the plasma neuro peptide Y (NPY), which was reduced by HT, yucca reduced circulation cholecystokinin (CCK) and hypothalamic mRNA expression of CCK. Supplementation of yucca increased the mRNA expression of both heat and cool sensing receptor. The results of the present study indicate that yucca could improve antioxidant status, attenuate the heat stress response by regulating hypothalamic temperature-sensing genes in growing chickens. Besides, yucca supplementation improved feed intake probably through modulating CCK in growing broilers under high ambient temperature.